(untitled) (Revista Argentina de Musicología, 2018)
The myth about the origin of tango repeated with some variations that it was born in the suburbs, and within the peringundines were it was well-known by the “niños bien” (young men from the high class) who were eternal class transgressors. Banned and censored in Buenos Aires, but enshrined in Paris after 1910, tango made a triumphant return to Buenos Aires handled by Baron Antonio De Marchi, who presented it in 1913, in a social dance, at the Palais de Glace. Only then tango would have been accepted by the oligarchy and copied by the growing popular and middle classes. This myth of origin is persistent, but not true. Documents show something else, and it is worth to contrast different versions of the story, especially the chronics in magazines that show the existence of a very dynamic society that has no ghetto and accept the tango very quickly. The article describes the trajectory of the myth from the “peringundín” to Paris and shows with contemporary sources, that this myth that denies the contribution of immigration, does not resist the comparison with de archives.